Pengaruh Herding dan Religiosity Terhadap Keputusan Investasi Saham dengan Financial Literacy Sebagai Variabel Moderasi - Puspitasari, Putri; Ristianawati, Yuyun (Journal of Business and Economics Research (JBE), 2024)
This study aims to find out how the role of Herding and Religiosity affects Stock Investment Decisions with Financial Literacy as a moderation variable, on generation Z investors in Central Java. The sample was selected using a simple random sampling method and a sample of 40 stock investors in generation Z in Central Java was obtained. The data management technique uses partial least square (PLS) version 4.0 with Analysis Techniques in the form of descriptive statistics, outer models, and inner models. In conclusion, the findings of the study show that herding has a significant positive effect on stock investment decisions, with a T-statistical value of 2,596 > from the statistical rule of >1,967 with an original sample of 0.610 and a p-value of 0.010 < from 0.05. With a religiosity value has a significant positive effect on stock investment decisions, with a t-statistical value of 3,723 > from the statistical rule of >1, 967 with an original sample of 0.918 and a p-value of 0.918 < from 0.05. Meanwhile, financial literacy can moderate the influence of herding on investment decisions, with a t-statistical value of 2.895 > from the statistical rule of >1.967 with an original sample of 0.533 and a p-value of 0.004 < of 0.05. For investment decisions, with a t-statistical value of 3,490 > from the statistical rule of >1,967 with an original sample of -0.610 and a p-value of 0.001 < from 0.05.